Relation between CYP2C19 phenotype and genotype in a group of Brazilian volunteers - Rafael Linden; Ana Luiza Ziulkoski; Paula Tonello; Maína Wingert; André Arigony Souto (Universidade de São Paulo, 2009)
The CYP2C19 gene presents polymorphism affecting the pharmacokinetics of several drugs of clinical importance. The purpose of this study was to investigate the correlation between CYP2C19 genotype and metabolic phenotype in a group of 38 Brazilian volunteers, evaluating the phenotype prediction capacity of the genotyping procedure. For CYP2C19 phenotyping, omeprazole was used as the probe drug, using the hydroxylation metabolic ratio as the phenotypic indicator. Venous blood samples were drawn before and three hours after an oral administration of 20 mg omeprazole. The plasma concentrations of omeprazole and hydroxy-omeprazole were determined by high performance liquid chromatography. The genotyping assay was carried out using a Real-Time-PCR-based assay, identifying the alleles *1 (completely functional), *2, *3 and *4 (null). The phenotyping procedure estimated the presence of 4 poor, 34 extensive and 1 ultra-extensive metabolizer. The genotyping identified 4 poor, 23 extensive and 11 intensive metabolizers. The groups of volunteers classified according to the number of active alleles of CYP2C19 had significant differences in the metabolic ratios of omeprazole hydroxylation. However, volunteers exhibiting the same number of active alleles presented different phenotypes. Therefore, the phenotyping of CYP2C19 is a more promising alternative to dose individualization of CYP2C19 substrate drugs. O gene CYP2C19 apresenta polimorfismo genético, com impacto importante na farmacocinética de diversos fármacos de importância clínica. O objetivo deste estudo foi avaliar a correlação entre genótipo e fenótipo de CYP2C19 em um grupo de 38 voluntários brasileiros, avaliando a capacidade de predição do fenótipo a partir de testes de genotipagem. Para a fenotipagem, utilizou-se omeprazol (OME) como fármaco-sonda para CYP2C19, empregando sua razão metabólica de hidroxilação como indicador fenotípico. Amostras de sangue foram coletadas antes e três horas após a administração oral de 20mg do fármaco. As concentrações plasmáticas de OME e seu metabólito foram determinadas por cromatografia líquida de alta eficiência. A genotipagem de CYP2C19 foi realizada através de ensaio baseado na reação em cadeia da polimerase em tempo real, identificando os alelos *1 (completamente funcional),*2 e *3 (nulos). Pela fenotipagem foi possível estimar a presença de 3 metabolizadores lentos, 34 rápidos e 1 ultra-rápido; enquanto pela genotipagem foi determinada a presença de 4 metabolizadores lentos, 23 rápidos e 11 intermediários. Os grupos de voluntários classificados de acordo com o número de alelos ativos apresentaram diferenças significativas entre as razões metabólicas de hidroxilação de omeprazol. Entretanto, indivíduos com o mesmo genótipo apresentaram fenótipos diferentes. Desta forma, a fenotipagem apresenta-se como alternativa mais promissora para a individualização das doses de fármacos substratos de CYP2C19.